(untitled) (Global Journal of Science Frontier Research, 2018)
To explain the weight reduction of a charged capacitor and Einstein’s unification, it is necessary to confirm the existence of the repulsive charge-mass interaction and the attractive current-mass interaction. Therefore, to show the existence of the current-mass interaction, one must measure the effect of a small directional dependence of weight for a magnet, To do this, one must exclude the magnetic effect from the earth. In addition, one should avoid the influence of the magnet to the electronic scale for weighing. Here, we provide a method to measure and confirm such tiny effects of weight directional dependence experimentally. However, it is not effective to measure the small current-mass interaction directly. A problem is that a current must have a maintaining source unless in the super-conducting situation. Thus, this connection to the source would affect the measurements of the small current-mass interaction. Moreover, E = mc 2 is not always valid and Einstein failed his unification because, unlike Maxwell, he did not recognize that some additional interactions must be added to the original theories.